MOBILE GAME HALMA MULTIPLAYER - Novrido Charibaldi; Wilis Kaswidjanti; Muhammad Dhimas (Telematika, 2010)
Handphone besides as a communication tool also has a function as a medium of entertainment. Various multimedia services and communications facilities contained therein, one Bluetooth. Games is one application that always exist in the mobile phone, and with a wider variety of games development by utilizing the services in mobile. In this research, the development of the multiplayer games for mobile phones utilizing Bluetooth communication media using the programming language Java Micro Edition (J2ME). Design method using the grapple, NetBeans IDE 6.1 is used as tools to assist programming.